Analisis Praktik Pembiayaan Musyarakah di Baitul Maal wat Tamwil Saudara Grabag Magelang: Perspektif Fatwa DSN MUI No. 08/DSN-MUI/IV/2000 - Afifah, Umi; Purwanto; Fitriyani, Yeny (AL-SULTHANIYAH, 2025)
This study aims to assess the suitability of musyarakah financing practices at BMT Saudara Grabag Magelang based on DSN-MUI Fatwa No. 08/DSN-MUI/IV/2000. Musyarakah financing is a collaboration between shahibul maal and mudarib that contributes positively to MSMEs. However, inconsistencies were found in practice, especially in terms of loss sharing and profit sharing calculations. Losses are not shared according to the proportion of each party's capital contribution, and profit sharing does not always reflect the agreed ratio. BMT Saudara also applies rescheduling to handle losses, which is contrary to the principle of musyarakah which requires proportional loss sharing. This study uses a descriptive method with interactive analysis techniques, based on primary data from interviews and observations of 1 teller, 1 manager, and 5 customer members. The results show that although sharia aspects such as ijab qabul, legal capacity, object of the contract, and dispute resolution have been implemented, there are still shortcomings in the implementation of profit and loss sharing. The study recommends that BMT Saudara adjust the practice to be more in accordance with sharia principles and the DSN-MUI fatwa.